STRENGTHENING LOCAL IDENTITY IN THE DIGITAL ERA THROUGH SMART VILLAGE KKN AND ABCD-BASED LOCAL WISDOM IN PADANG KALUA VILLAGE - Nur Hafifa, Cahayu; Rheyhan Aulia Putri; Dinda Pasafia A; Indri Duwi Antika; Nadia Vega; Aidatul Fatwa; Miftahul Jannah Ahyar; Hamsirah; Fuji Raodah; Siti Maryam; Andi Muhammad Haikal; Rahmat Ramadhan Amir; Nilam Permatasari Munir; Andi Musafir Rusyaidi (International Journal of Multidisciplinary Reseach, 2025)
Community Service Program (Kuliah Kerja Nyata/KKN) is an implementation of the Tri Dharma of Higher Education in the form of community engagement oriented toward empowerment and sustainable development. This study aims to examine the implementation of a Smart Village KKN based on the Asset-Based Community Development (ABCD) approach in strengthening local community identity in the digital era in Padang Kalua Village, Bua District, Luwu Regency, South Sulawesi Province. The ABCD approach was applied through the stages of discovery, design, define, and reflection, involving active participation from the village community. Data collection methods included observation, in-depth interviews with village officials and community leaders, and documentation of activities. The results of the KKN implementation indicate that the ABCD approach is effective in optimizing the utilization of local assets through several priority programs, including the development of a village website and digital village accounts (Digides) as online-based public service platforms, the creation of asset-mapping infographics to enhance transparency and community participation, and the production of digital educational videos related to digital literacy and cybersecurity. These programs contributed to improving the efficiency of administrative services, strengthening accountable village governance, and enhancing community readiness to face digital transformation without abandoning local wisdom values. Therefore, the ABCD-based Smart Village KKN in Padang Kalua Village can serve as a model of sustainable village empowerment rooted in the community’s local potential and identity.